2022
DOI: 10.30595/pspfs.v4i.498
|View full text |Cite
|
Sign up to set email alerts
|

Fertilitas, Daya Tetas Telur dan Sintasan Larva Ikan Tawes (Barbonymus gonionotus) pada Media Pembuahan Larutan NaCl Fisiologis dan Madu dengan Dosis Berbeda

Abstract: Salah satu masalah yang timbul pada usaha pembenihan Ikan tawes (Barbonimus gonionotus) adalah rendahnya fertilisasi sperma yang disebabkan oleh rendahnya motilitas dan viabilitas sperma. Upaya untuk mengatasi hal tersebut adalah dengan menggunakan larutan NaCl Fisiologis dan madu yang dapat mendukung motilitas dan viabilitas spermatozoa. Tujuan penelitian ini adalah mengetahui pengaruh penambahan madu pada media pembuahan telur ikan tawes terhadap fertilitas, daya tetas telur dan sintasan larva ikan tawes. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
0
0
Order By: Relevance
“…The results of research on pond A which used a 1:1 male to female ratio showed that male fish sperm was not enough to fertilize all of the female's eggs so that the seeds produced tended to be few with an average of 68%. This is in line with research by Savitri et al, (2022) who found that the hatchability of Tawes fish eggs for a 1:1 broodstock ratio was in the range of 51%-66%. Based on observations in pond B which used a male ratio of 2: 1 female, male Tawes sperm could fertilize all the eggs that came out of the female's stomach so that the seed yield obtained was higher than the other three treatments, namely 89%.…”
Section: Discussionsupporting
confidence: 92%
“…The results of research on pond A which used a 1:1 male to female ratio showed that male fish sperm was not enough to fertilize all of the female's eggs so that the seeds produced tended to be few with an average of 68%. This is in line with research by Savitri et al, (2022) who found that the hatchability of Tawes fish eggs for a 1:1 broodstock ratio was in the range of 51%-66%. Based on observations in pond B which used a male ratio of 2: 1 female, male Tawes sperm could fertilize all the eggs that came out of the female's stomach so that the seed yield obtained was higher than the other three treatments, namely 89%.…”
Section: Discussionsupporting
confidence: 92%